Tranexamic Acid Administered During Off-Pump Coronary Artery Bypass Graft Surgeries Achieves Good Safety Effects and Hemostasis - Wang, Enshi; Yuan, Xin; Wang, Yang; Chen, Weinan; Zhou, Xingtong; Hu, Shengshou; Yuan, Su (Frontiers in Cardiovascular Medicine, 2022)
Background: Tranexamic acid (TXA) administered during off-pump coronary artery bypass (OPCAB) surgeries has achieved good blood control in small cohorts. We aimed to investigate the safety issues and hemostasis associated with TXA administration during OPCAB in a large retrospective cohort study. Methods: This study included 19687 OPCAB patients from 2009 to 2019. A total of 1307 patients were excluded because they were younger than 18 years or certain values were missing. Among the remaining 18380 patients, 10969 were in the TXA group and 7411 were in the no-TXA group. There were 4889 patients whose TXA dose was ≥ 50 mg/kg, and the remaining 6080 patients had a TXA dose of < 50 mg/kg. Propensity score matching was performed between the TXA and no-TXA groups and between the high-dose and low-dose groups, and statistical analysis was performed. Results: TXA administration did not increase the risk of hospital death or thromboembolic events. Patients administered TXA had less blood loss at 24 hours (478.32±276.41 vs. 641.28±295.09, p<0.001) and 48 hours (730.59±358.55 vs. 915.24±390.13, p<0.001) and total blood loss (989.00±680.43 vs. 1220.01±720.68, p<0.001) after OPCAB than the non-TXA patients. Therefore, the risk of total blood exposure (OR=0.50, 95% CI 0.47-0.54, p < 0.001) or blood component exposure (p < 0.001) decreased significantly in the patients administered TXA. The TXA dosage did not impact the patient survival, thromboembolic events or blood management. Conclusions: The application of TXA was safe and provided blood control in patients with OPCAB, and the dosage did not affect these parameters.